Molecular transport of benzene and methyl-substituted benzenes into filled natural rubber sheets - Unnikrishnan G; Thomas Sabu (Journal of Applied Polymer Science, 1996)
Sorption and diffusion of benzene and methyl-substituted benzenes were investigated through natural rubber reinforced with four types of carbon black : superabrasion furnace, intermediate superabrasion furnace, high-abrasion furnace and semi-reinforcing furnace. The rubber loaded with superabrasion furnace took the lowest amount of solvents among all the samples. It was observed that the mechanism of transport deviates from the normal Fickian trend with a decrease in particle size of the fillers. The diffusion coefficients were determined considering the changes in thickness as well as the diameter of the natural rubber samples. From the temperature dependence of diffusivity, the activation energy for the diffusion process was computed. The sorption data were used to estimate the rubber solvent interaction parameter, enthalpy and entropy of the sorption process.
Keywords: Benzene; Methyl-substitued benzene; Natural rubber